Reactive Oxygen Species Deficiency Due to Ncf1-Mutation Leads to Development of Adenocarcinoma and Metabolomic and Lipidomic Remodeling in a New Mouse Model of Dextran Sulfate Sodium-Induced Colitis - Carvalho, Lina; Gomes, Joana R. M.; Tavares, Ludgero C.; Xavier, Ana R.; Klika, Karel D.; Holmdahl, Rikard; Carvalho, Rui A.; Souto-Carneiro, M. Margarida (Frontiers in Immunology, 2018)
Inflammatory bowel disease is characterized by chronic relapsing idiopathic inflammation of the gastrointestinal tract and persistent inflammation. Studies focusing on the immune-regulatory function of reactive oxygen species (ROS) are still largely missing. In this study we analysed a ROS-deficient mouse model leading to colon adenocarcinoma. Colitis was induced with dextran sulfate sodium (DSS) supplied via the drinking water in wild-type (WT) and Ncf1-mutant (Ncf1) B10.Q mice using two different protocols, one mimicking recovery after acute colitis and another simulating chronic colitis. Disease progression was monitored by evaluation of clinical parameters, histopathological analysis and the blood serum metabolome using 1H NMR spectroscopy. At each experimental time point, colons and spleens from some mice were removed for histopathological analysis and internal clinical parameters. Clinical scores for weight variation, stool consistency, colorectal bleeding, colon length and spleen weight were significantly worse for Ncf1 than for WT mice. Ncf1 mice with only a 7-day exposure to DSS followed by a 14-day resting period developed colonic distal high-grade dysplasia in contrast to the low-grade dysplasia found in the colon of WT mice. After a 21-day resting period, there was still β-catenin-rich inflammatory infiltration in the Ncf1 mice together with high-grade dysplasia and invasive well-differentiated adenocarcinoma, while in the WT mice, high-grade dysplasia was prominent without malignant invasion and only low inflammation. Although exposure to DSS generated less severe histopathological changes in the WT group, the blood serum metabolome revealed an increased fatty acid content with moderate-to-strong correlations to inflammation score, weight variation, colon length and spleen weight. Ncf1 mice also displayed a similar pattern but with lower coefficients and showed consistently lower glucose and/or higher lactate levels which correlated with inflammation score, weight variation and spleen weight. In our novel DSS-induced colitis animal model, the lack of an oxidative burst ROS was sufficient to develop adenocarcinoma and display altered blood plasma metabolic and lipid profiles. Thus, oxidative burst seems to be necessary to prevent evolution towards cancer and may confer a protective role in a ROS-mediated self-control mechanism.